Influence of boundary conditions on the prediction of springback and wrinkling in sheet metal forming. (March 2017) - Neto, D.M.; Oliveira, M.C.; Santos, A.D.; Alves, J.L.; Menezes, L.F.
Abstract: The high-strength steel sheets currently used in the automotive industry are prone to non-traditional behaviour during forming, being wrinkling and springback two of the most challenging geometrical predictions for numerical simulation. Thus, the finite element method requires accurate and reliable numerical models. This study presents the experimental and numerical analysis of a rail component with high tendency to develop wrinkling and 2D springback. Two different materials are used for the sheet blank, namely a mild steel (DC06) and a dual phase steel (DP600). The frictional behaviour between each metallic sheet and the forming tools is evaluated through the flat-die test, allowing the determination of a friction coefficient as a function of the normal pressure. The influence of the applied boundary conditions on the numerical results is evaluated by means of two distinct numerical models (full blank geometry and 1/4 of the blank with symmetry conditions). The results show that the wrinkling behaviour is strongly affected by the blank's material, as well as by the symmetry conditions defined in the numerical model. In fact, considering the full model of the blank, the numerical results are in better agreement with the experimental ones. However, the computational cost of the numerical simulation considering the full blank is substantially higher than using 1/4 of the blank. Highlights: Experimental and numerical analysis of wrinkling in sheet metal forming. Comparison between a mild steel (DC06) and a dual phase steel (DP600). Frictional behaviour evaluated through the flat-die test. Influence of the applied boundary conditions on the developed wrinkle shape. Numerical results in good agreement with the experimental ones.